Analisis Kecerdasan Emosional Pemain Nuhafa Futsal Training Rimbo Bujang - Wahyu Adi Nugroho; Jhony Hendra; Titis Wulandari (CV. Master Literasi Indonesia, 2025)
This research is motivated by the fact that emotional intelligence in early childhood tends to be very low due to their relatively young age. This lack of emotional intelligence in children is caused by coaches who do not provide specific guidance to children before playing futsal and the lack of a specifically designed program, such as mental, technical, and physical training. This lack of emotional intelligence in players leads to poor concentration, team spirit, and performance skills. The purpose of this study was to determine the emotional intelligence of futsal players at Nuhafa Futsal Training Rimbo Bujang. Based on the research results, it was found that there were problems in the emotional intelligence of players as seen from 4 indicators of emotional intelligence, namely: 1) Recognizing one's own emotions, players have not been able to recognize and understand their own emotions, often express anger without control, and do not receive special training in emotional aspects. 2) Managing emotions, players have difficulty controlling emotions when under pressure, tend to be rude and unsportsmanlike, which is detrimental to the team in the match. 3) Motivating oneself, the majority of players are less able to raise their spirits independently and still depend on external motivation (coaches/friends). and 4) Recognizing other people's emotions (empathy), players are less sensitive to the emotions of their colleagues, rarely provide support, and show low empathy in teamwork. By using these indicators, players have not been able to control their emotions well, this triggers chaos in a game which results in their poor performance in the match.